The Oxford handbook of organizational identity - Pratt, Michael G.; Schultz, Majken; Ashforth, Blake E.; Ravasi, Davide, 1970- (Oxford : Oxford University Press, 2016)
Identity studies focus on how organisations define themselves and what they stand for in relation to internal and external stakeholders. This handbook offers an introduction to the growing field of organisational identity and a broad range of the most important theories and methods for the study of organisational identity.
How Do We Communicate Who We Are? / Beth Schinoff, Kristie Rogers, Kevin G. Corley -- Materiality and Identity / Lee Watkiss, Mary Ann Glynn -- Fostering stakeholder identification through expressed organizational identities / Cindi Baldi, Caroline Bartel, Janet Dukerich -- Identity Construction in Mergers and Acquisitions / Janne Tienari, Eero Vaara -- Organizational Identity in Institutional Theory / Mattew Kraatz, Nelson Phillips, Paul Tracey -- Organizational identity work / Glen E. Kreiner, Chad Murphy -- Organizational identity and innovation / Callen Anthony, Mary Tripsas -- Making Sense of Who We Are / Daan van Knippenberg -- Great debates in organizational identity study / Peter O. Foreman, David A. Whetten -- Optimal Distinctiveness Revisited / Ezra W. Zuckerman -- Organizational Identity: A Critique / Mats Alvesson, Maxine Robertson -- Bridging and Integrating Theories on Organizational Identity / Joep Cornelissen, Mirjam Werner, S. Alexander Haslam -- Organizational identity and organizational identity work as valuable analytical resources / Tony J. Watson -- Organizational Identity: The Significance of Power and Politics / Kate Kenny, Andrea Whittle, Hugh Willmott -- Re-Membering / Roy Suddaby, William Foster, Christine Quinn Trank -- Measuring Organizational Identity / Dennis A. Gioia, Aimee L. Hamilton -- Organizational Identity and Institutional Forces / Marya L. Besharov, Shelley L. Brickson -- Organizational Identity and the undesired self / Kimberly D. Elsbach, Janet Dukerich -- Planned Organizational Identity Change / Cees B. M. van Riel, Mamta Bhatt, Marijke Baumann -- Mobilizing Organizational Action Against Identity Threats / Jennifer Petriglieri, Beth A. Devine -- Institutional Pluralism, Inhabitants, and the Construction of Organizational and Personal Identities / Rich Dejordy, W. E. Douglas Creed.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Organizational sociology